Characterizing the complete mitochondrial genome and rDNA of Oestrus sp. (Diptera: Oestridae): the bot fly parasitizing the Iberian ibex, Capra pyrenaica - Aleix-Mata, Gal; Granados, Jos E.; Montiel, Eugenia E.; Caparrs, Noelia; Mora, Pablo [UNESP]; Rico-Porras, Jos M.; Mendoza, Einer F.; Prez, Jess M.; Snchez, Antonio (Oxford University Press (OUP), 2025)
Species of the genus Oestrus Linnaeus, 1758 (Diptera: Oestridae) are obligate parasites that affect the nasal and pharyngeal cavities of mammals, causing significant harm to both livestock and wildlife. In this study, the complete mitogenome of Oestrus sp., a bot fly parasitizing the Iberian ibex (Capra pyrenaica Schinz, 1838), has been sequenced and assembled. A comparison with the mitogenome of Oestrus ovis Linnaeus, 1758 revealed a high degree of similarity in terms of gene organization and nucleotide composition, and phylogenetic analyses confirmed the close evolutionary relationship between them. Additionally, the entire rDNA cistron, including the internal transcribed spacers (ITS1 and ITS2), was characterized for both species, revealing considerable variation in the length of ITS1, while the 18S, 5.8S, and 28S rRNA genes showed high sequence conservation. These results provide information about molecular markers of 2 Oestrus species. Furthermore, the findings offer insights that could facilitate the diagnosis and management of parasitic infestations of Oestridae species in both domestic and wild hosts.